Respiratory tract excretion of cytomegalovirus in Thai children - Lloyd C. Olson (2018)
Cytomegalovirus has been found to be commonly present in the respiratory tract secretions of Thai children. Eleven per cent of children with pertussis syndrome, 18.1 per cent of 342 children with respiratory tract infections, and 15.1 per cent of well babies were positive for cytomegalovirus. Virus was most commonly present in children less than one year of age, the incidence falling progressively with age so that it was unusual to recover cytomegalovirus from children over the age of 4 years. Most patients tested possessed serum neutralizing and immunoglobulin M antibody at the time virus was being excreted, but few had complement-fixing antibody. © 1970 The C. V. Mosby Company.